2015
DOI: 10.1063/1.4929813
|View full text |Cite
|
Sign up to set email alerts
|

Semi-local scaling and turbulence modulation in variable property turbulent channel flows

Abstract: We theoretically and numerically investigate the effect of temperature dependent density and viscosity on turbulence in channel flows. First, a mathematical framework is developed to support the validity of the semi-local scaling as proposed based on heuristic arguments by Huang, Coleman, and Bradshaw ["Compressible turbulent channel flows: DNS results and modelling," J. Fluid Mech. 305, 185-218 (1995)]. Second, direct numerical simulations (DNS) of turbulent channel flows with different constitutive relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 30 publications
12
107
0
Order By: Relevance
“…Similar observations can be made for cases LL and VλSPr LL , which have quasisimilar Pr but different Re τ . Although not shown here, it should be noted that, similar to statistics of velocity fluctuations discussed by Patel et al [15], it was found that ρθ 2 ≈ ρθ 2 , but ρ 1.5 θ 3 = ρ 1.5 θ 3 . This highlights the importance of including density fluctuations in third-order moments, because of the functional relation between density and temperature, which causes a preferential concentration of a high-density fluid in a low-temperature streak, and vice versa.…”
Section: E Higher Order Scalar Statisticsmentioning
confidence: 77%
See 3 more Smart Citations
“…Similar observations can be made for cases LL and VλSPr LL , which have quasisimilar Pr but different Re τ . Although not shown here, it should be noted that, similar to statistics of velocity fluctuations discussed by Patel et al [15], it was found that ρθ 2 ≈ ρθ 2 , but ρ 1.5 θ 3 = ρ 1.5 θ 3 . This highlights the importance of including density fluctuations in third-order moments, because of the functional relation between density and temperature, which causes a preferential concentration of a high-density fluid in a low-temperature streak, and vice versa.…”
Section: E Higher Order Scalar Statisticsmentioning
confidence: 77%
“…As shown in previous works [11,12,15,16,23,24,30], the semilocal wall coordinate y is effective in accommodating changes in viscous scales due to variable properties, thus providing a meaningful representation for the turbulent velocity statistics. Therefore, all wall-normal profiles are plotted as a function of y in the present work.…”
Section: Scalar Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mixed scaling (recently discussed in [22]) has proven to give quite satisfactory results in collapsing first-and second-order moments [21] obtained from a wide range of M Bw . We recall that in case of an incompressible flow, Re τ * = Re τ .…”
Section: Supersonic Turbulent Channel Flowmentioning
confidence: 99%